Postdigital Theologies: Technology, Belief, and Practice - Savin-Baden, Maggi; Reader, John (Postdigital Science and Education, 2022)
Part 1 Postdigital theologies -- Chapter 1 Introduction - Maggi Savin-Baden and John Reader -- Chapter 2 Landscapes of Postdigital Theologies -- Chapter 3 Interview with Catherine Keller – Petar Jandric -- Chapter 4 Community and communion in a postdigital world – Andrew Braddock -- Chapter 5 The Generative and Explanatory Potential of the Bible within Postdigital Discourse - Rebecca Dean -- Part 2 Postdigital conundrums -- Chapter 6 Divine Becoming in the Postdigital - John Reader -- Chapter 7 Unlikely Allies? Transhuman Dignity and Catholic Theology on Flourishing -- Alcibiades -- Chapter 8 Provoked by the Divine: The Event of the Postdigital Sublime – Eric Trozzo -- Chapter 9 Queering Postdigital Presence: Digital Afterlife as a Technology of Queer Continuity and Transformation – Jack Slater -- Chapter 10 Untitled Steve Fuller -- Part 3 Language, machines and theologies -- Chapter 11 Postdigital Humans: Technology and Divine Design - Douglas Estes -- Chapter 12 Machine Learning and Spiritual Wisdom for Contemporary Urban Environments -- - Paul Woods -- Chapter 13 Postdigital Theologies: A closer inspection of the way language is employed in digital discourses. – Simon Cross -- Chapter 14 Sacramental Engines: Charles Babbage and the Elements of Postdigital Theology- Ryan Haecker -- Part 4 The impact of the digital -- Chapter 15 When the Church Embraced a Posthuman Future: How Pastoral Negotiations with Technology During the Covid-19 Pandemic Resulted in an Implicit Acceptance of Posthumanism - Heidi Campbell -- Chapter 16 God Made Better: How the Quest for Human-Level AI Reshapes Postdigital Divinity - Agana-Nsiire Agana -- Chapter 17- Curiosity as a spirit of religious transcendence in the postdigital and post-trans-humanism era – Paulo Quadros. .